New Syllabus Mathematics for O-Level 2 - Macmillan; Perry Joyce; Perry Owen (1979)
A complete revision course for the O-Level 2 modern mathematics syllabus as set by the major boards. Preface, Notation, Quadratic Functions, Trigonometry, Variation and Kinematics and Further Graphs, Coordinate Geometry and Calculus, Vectors and Transformations, Binary Operations and Finite Arithmetic and Groups, Further Case Geometry, Geometry and Trigonometry in Three Dimensions, Answers to Exercises, Index.